Customer Satisfaction and Buying Decision Influencing Competitive Advantage in Cement Paper Bags Industry - Fua, Jin Hoe (2023)
The history of cement paper bags industry culture diversity and evolutionary had greatly affected by its market demand changed domestically and internationally. Current issues on demand of cement paper bags may due to changing of major paper bags customer sales strategy to focus more on the tanker sales from bagged cement can furtherly reduce the yearly demand on paper bags consumption even though the country infrastructures projects are still carry on. The paper bags cost is one the major costs elements in their packing activity however the customers are trying to reduce it down to the lowest possible. This is due to the yearly demand paper bags by some of these key cement producers is more than ten million bags. The paper bags producers are to be alerted by this issues what is their counter measures. The new entry into this paper bags market from other nearby countries is unpredictable in the coming future when market demand of paper bags is back to normal level by referring to the Portland cement demand report. The strategic sales plans to build the barrier of entry to defend must be prepared as early as possible by the paper bags producers and to examine the factors could influence customer satisfaction, supplier selection, industrial buying decision, customer detention and loyalty and competitive advantageous, anti-competition policy to reduce fiercer competition from expanding further inside the domestic market and ESG compliance to enhance sales need to study in order to place them on strong competition position inside the supply market. The cement paper bags industry is considered not a very capital intensive industry. Hope this is also a research gap for this particular type of industry. Paper bags costs and paper bags performance could be the very sensitive issues to this types of industry buyers. This is because when customer benefit is being affected. Conducting an annual customer satisfaction survey is deemed necessary for the continuous development of the suppliers’ supply chain management. In so many years backward they were many researchers interested to focus on factors might affect buyer satisfaction before drawing up their buying decision dedicated to any single factor or two to publish in their articles for other new researcher to refer or to conduct further research. Their analysis is mainly concentrated on market orientation measurement but is not that specific to this type of paper bags industry. Therefore, the empirical results revealed by this research study from N=70 and N=20 were duly analyzed. The data demonstrated that main conclusions which led the researcher the autonomous factors and ward factor exerts directly on the degree of paper bags customers satisfaction with their suppliers reliability. Besides this, the outcome results of the data and thematic analyses also drive the researcher to propose the implication for future research areas relative to paper bags industry on customer satisfaction, supplier selection and making of buying decision in order to enhance the customer relationships with their own customers. The methodologies to be applied in this research paper are the two main versions of mixed methods of quantitative by data analysis and qualitative by thematic analysis. Hope this research paper will provide some constructive results and new ideas for upcoming research study to base on current situation and future prospects of the cement paper bags industry development. The main role to play is the industrial demand which is depended on the volume of sales from the paper bags customers.